Comparison of the Success Rate of Endodontic Treatment and Implant Treatment. (24th August 2011) - Elemam, Ranya Faraj; Pretty, Iain
Abstract : Dentists and patients are facing a perplexity between saving a compromised tooth through endodontic treatment and restoration or by extraction and replacement with an implant. The purpose of this paper was to compare the success rates of these two treatments. Success was measured as the longevity of the tooth or implant. Studies which met strict inclusion criteria to ensure best evidence were included. Searches were performed in Ovid Medline, Pubmed, Scopus database, and the Cochrane Library. Evidence-based groups were formed following the assessment of inclusion/exclusion criteria. The overall success rates for primary endodontic, nonsurgical retreatment, and surgical treatment were (86.02%), (78.2%), and (63.4%), respectively, implants was 90.9%. In conclusion, choice between implant and endodontic therapy cannot be exclusively based on outcome as both treatments differ in the biological process, diagnostic modalities, failure patterns, and patients preferences. More research is required with improved study designs before long-term success rates can be compared.